Public management and fiscal indicators: a performance analysis of the municipalities of Pernambuco (Research, Society and Development, 2022)
The good management of public resources is an instrument for the achievement of better socioeconomic development conditions. This work aims to evaluate the financial and budgetary performance of the 10 most populated municipalities of the State of Pernambuco, referring to the fiscal year 2021. As methodology it was used the 9 fiscal indicators proposed by the National Treasury Secretariat (NTS) in its Bulletin of Finances of the Subnational Entities. It is used the documental analysis in the process of obtaining the data, through the Accounting and Fiscal Information System of the Brazilian Public Sector (Siconfi). The main results demonstrate that the biggest municipalities of the sample have higher levels of debt and expenses with debt service, as a proportion of the net current revenue, than the smaller municipalities. Another important result is the demonstration of the degree of dependence of the municipalities in relation to intergovernmental transfers, most municipalities of the sample have on average only 30% of own collection. The work contributes to the literature by extending the application of the NTS indicators beyond the States and capitals, demonstrating the functionality of the 9 indicators to analyze the performance of municipalities of various sizes. Furthermore, the article innovates by proposing the Fiscal Management Competitiveness Index as an aggregator index of the results of the 9 indicators, enabling the constitution of a final ranking among the municipalities analysed.